2012
DOI: 10.1242/jeb.074427
|View full text |Cite
|
Sign up to set email alerts
|

Fatiguing stimulation of one skeletal muscle triggers heat shock proteins activation in several rat organs: the role of muscle innervation

Abstract: SUMMARYWe hypothesised that activation of muscle afferents by fatigue triggers a widespread activation of heat shock proteins (HSPs) in resting muscles and different organs. In anaesthetised rats, HSP25 and HSP70 levels were determined in both tibialis anterior (TA) and extensor digitorum longus (EDL) muscles and in the diaphragm, kidney and brain by ELISA, which mostly identifies phosphorylated HSP, and western blotting. One TA muscle was electrically stimulated and tissues were sampled 10 or 60min after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…The present study confirms our observations that fatigue of a single hindlimb muscle elicits a widespread pHSP25 response triggered by the activation of muscle afferents from the stimulated TA muscle (Jammes et al, 2012). The new findings are: (1) the groups III and IV muscle afferents from the stimulated TA muscle play key roles in the widespread pHSP25 response but the stimulation of group IV afferents is only able to induce pHSP25 activation in organs in the trunk (diaphragm, kidney) and brain; (2) the demonstration of the key role played by the adrenoreceptor simulation in the widespread pHSP25 response to TA stimulation in all samples tissues, except in the brain; (3) the absence of a glutamatergic pathway responsible for the HSP25 response.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study confirms our observations that fatigue of a single hindlimb muscle elicits a widespread pHSP25 response triggered by the activation of muscle afferents from the stimulated TA muscle (Jammes et al, 2012). The new findings are: (1) the groups III and IV muscle afferents from the stimulated TA muscle play key roles in the widespread pHSP25 response but the stimulation of group IV afferents is only able to induce pHSP25 activation in organs in the trunk (diaphragm, kidney) and brain; (2) the demonstration of the key role played by the adrenoreceptor simulation in the widespread pHSP25 response to TA stimulation in all samples tissues, except in the brain; (3) the absence of a glutamatergic pathway responsible for the HSP25 response.…”
Section: Discussionsupporting
confidence: 92%
“…The present study was limited to the measurements of the changes in pHSP25. Indeed, we have already shown that the pHSP25 level increased very early after the fatiguing muscle stimulation had ended, preceding the increase in HSP70 and non-phosphorylated HSP25 (Jammes et al, 2012).…”
Section: Research Articlementioning
confidence: 73%
See 3 more Smart Citations